Comparing subjective well‐being and health‐related quality of life of Australian drug users in treatment in Regional and Rural Victoria. (6th March 2014) - Miller, Peter G.; Hyder, Shannon; Zinkiewicz, Lucy; Droste, Nicolas; Harris, Jane B.
Abstract Introduction and Aims The aim of this study is to examine the self‐reported subjective well‐being and health‐related quality of life (HRQOL) of alcohol and other drug users and to examine whether subjective well‐being in this sample would be predicted by either HRQOL and/or severity of dependence. Design and Methods A cross‐sectional survey was conducted of 201 Victorian substance users in individual targeted outpatient treatment for a variety of types of substance use. Participants were administered an interview, including the personal well‐being index, the SF‐8 health survey and the severity of dependence scale, in order to assess subjective well‐being, the mental health component of HRQOL and severity of drug dependence respectively. Results Subjective well‐being was predicted by mental health aspects of HRQOL (sr2 = 0.03) and by employment (sr2 = 0.05), rather than by severity of dependence [F(5, 146) = 5.60, P < 0.001, R2 = 0.14]. Discussion and Conclusions The current sample of urban and regional substance users in outpatient treatment shows poorer levels of subjective well‐being than do the general population. Subjective well‐being was predicted by mental aspects of HRQOL and not by severity of drug dependence or by physical aspects of HRQOL. Treatment which aims to improve substance users' well‐being should include mental health interventions and pathways to employment. [Miller PG, Hyder S, Zinkiewicz L, Droste N, Harris JB. Comparing subjective well‐being and health‐related quality of life of Australian drug users in treatment in Regional and Rural Victoria. Drug Alcohol Rev 2014;33:651‐657]